PEMBERIAN PUPUK KOMPOS JERAMI PADI DAN KALIUM UNTUK PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) VARIETAS TOPAZDI PEMBIBITAN UTAMA - Exfan Mafror; Sukemi Indra Saputra; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The aim of this research was to determine the effect ofrice straw compostand potassium, andits combination with the right doseof the growth of oil palm seeds in main nursery. The research was conducted at the experimental farm of Agriculture Faculty, Universityof Riau, Bina Widy astreet, district of Tampan, Pekanbaru City. This research was conducted on April until June 2014. This research arranged experimentally using Completely Randomized Design (CRD) with two factorial. The first factor is compostedrice straw(0, 75, 100and125g/plant), second factor is potassium(0, 0,825, 1,10and 1,375 g/plant) were repeated 3 times. Data were analyzed using analysis of variance (ANOVA) andfollowed byDuncan’s test at 5% level. Parameters measured were theincrease of seeds height, increase of seeds hump diameter, increase of leaves number, increase of leaf midrib length and increase of leaf width. The results showedthat giving rice straw compostand potassiumand it combination not revealgood growth toall parameters but thesingle factor of potassiumgavegood resultsatincrease of seeds height, increase of seeds stump diameter and increase of leafmidrib length atdose of0,825g/plant. Keywords: rice strawcompost, potassium, oil palm seeds, main nursery